Koncepcja zachowania kapitału a wartość godziwa - Markiewicz-Rudnicka, Dominika (Idea of Capital Keeping versus Equitable Value, 2007)
The purpose of the paper is to indicate that precision equity definition influences the source of information quality about its value. The aim of this paper is to answer one question: Does applying the right equity definition and the equity theory determinate methods of valuation asset in entity?
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1158, s. 245-252